Technological Constraints Perceived by Dairy Entrepreneurs (Indian Journal of Extension Education, 2015)
The present study was undertaken to find out the technological constraints faced by the dairy cooperative society members and non-members in adoption of advanced dairy production technology. Atotal of 240 respondents (120 members and 120 non-members of dairy cooperative societies) were included in the sample of the study. The results of the study indicated that low draft capacity of crossbreed male, less area under fodder crops, shortage of water for green fodder production, inadequate and costly medicines, non-remunerative price of milk, low conception rate through A.I., non-availability of mineral mixture were the important constraints expressed by the members of dairy cooperative societies in the adoption of advanced dairy production technology. Whereas, non-members of dairy cooperative societies also perceived similiar constraints with different level of severity.